2020
DOI: 10.1158/0008-5472.can-19-2332
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 Hampers Tumor Surveillance of Liver-Resident and Conventional NK Cells by Disrupting PI3K Signaling

Abstract: ◥Natural killer (NK) cells are enriched within the liver. Apart from conventional NK (cNK) cells, recent studies identified a liverresident NK (LrNK) subset, which constitutes about half of hepatic NK cells and exhibits distinct developmental, phenotypic, and functional features. However, it remains unclear whether and how LrNK cells, as well as cNK cells, participate in the development of hepatocellular carcinoma (HCC) individually. Here, we report that both LrNK and cNK cells are significantly decreased in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 41 publications
(48 reference statements)
6
73
0
1
Order By: Relevance
“…TIM-3 blockade exacerbated the disease phenotype in experimental allergic encephalomyelitis animal models, indicating TIM-3 as a negative regulatory molecule ( 3 ). TIM-3 is widely expressed on immune cells, such as T cells, NK cells ( 46 ), DCs and monocytes/macrophages ( 47 , 48 ). The results of Yan et al strongly suggested that increased TIM-3 expression in monocytes/tumor-associated macrophages was positively correlated with higher tumor grades and the poor survival in patients with HCC ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…TIM-3 blockade exacerbated the disease phenotype in experimental allergic encephalomyelitis animal models, indicating TIM-3 as a negative regulatory molecule ( 3 ). TIM-3 is widely expressed on immune cells, such as T cells, NK cells ( 46 ), DCs and monocytes/macrophages ( 47 , 48 ). The results of Yan et al strongly suggested that increased TIM-3 expression in monocytes/tumor-associated macrophages was positively correlated with higher tumor grades and the poor survival in patients with HCC ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency could be due to the complexity and heterogenicity of tissue NK cells. Hepatic NK cells have been shown to have distinct functions in antiviral and antitumor immunity 64,65 . Further studies are needed to clarify the possible involvement of NK cells and other immune cells in IL‐37‐mediated tumoral angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the binding of the endogenous ligand PtdSer with TIM-3 induced the dysregulation of NK cells through interrupting the PI3K/mTORC1/p-S6 signaling pathway. Importantly, TIM-3 knockdown or antibody blockade reduced tumor growth and prolonged the overall survival of orthotopical liver tumor-bearing mice in an NK cell-dependent manner (79). TNF-α was reported to induce NK cell expression of TIM-3 and NK cell dysfunction via the NF-κB pathway.…”
Section: Tim-3mentioning
confidence: 99%
“…TIM-3 is highly expressed on peripheral NK cells from patients with various types of solid tumors, such as lung cancer, gastric cancer, and advanced melanoma, and correlates with NK cell dysfunction and exhaustion ( 76 78 ). Tumor-infiltrating NK cells in particular show upregulated TIM-3 expression, which can predict poor prognosis in patients with liver cancer, NSCLC, endometrial cancer, and other types of tumors ( 79 81 ). Both conventional NK cells and liver-resident NK cells from patients with liver cancer express high levels of TIM-3, accompanied by decreased capacity of cytokine production and cytotoxicity ( 79 ).…”
Section: The Key Nk Cell Checkpoint Receptors or Molecules That Contrmentioning
confidence: 99%
See 1 more Smart Citation